An Unusual Presentation of a Thyroid Malignancy: A Case Report - M, Irfan; A, Baharudin; A, Ananda Dorai (IIUM Medical Journal Malaysia, 2010)
Patient with thyroid mass rarely presents in emergency situation. It is because the nature of the mass is that it usually increases slowly in size. Thus, any surgical intervention can be planned electively. The most common condition that necessitates urgent intervention, is upper airway compromise due to sudden rapid increase in size of the swelling. This can be due to intralesional bleeding or superimposed infection on the enlarged gland. We report a case of urgent completion thyroidectomy performed to a patient with fungating recurrent papillary carcinoma who present with bleeding from the mass externally.